Using testing history to estimate HIV incidence in mothers living in resource-limited settings: Maximizing efficiency of a community health survey in Mozambique - Orvalho Augusto; Sheila Fernández-Luis; Laura Fuente-Soro; Tacilta Nhampossa; Elisa Lopez-Varela; Ariel Nhacolo; Edson Bernardo; Helga Guambe; Kwalila Tibana; Adelino Jose Chingore Juga; Jessica Greenberg Cowan; Marilena Urso; et al. (Public Library of Science (PLoS), 2023)
Obtaining rapid and accurate HIV incidence estimates is challenging because of the need for long-term follow-up for a large cohort. We estimated HIV incidence among women who recently delivered in southern Mozambique by leveraging data available in routine health cards. A cross-sectional household HIV-testing survey was conducted from October 2017 to April 2018 among mothers of children born in the previous four years in the Manhiça Health Demographic Surveillance System area. Randomly-selected mother-child pairs were invited to participate and asked to present documentation of their last HIV test result. HIV-testing was offered to mothers with no prior HIV-testing history, or with negative HIV results obtained over three months ago. HIV incidence was estimated as the number of mothers newly diagnosed with HIV per total person-years, among mothers with a prior documented HIV-negative test. Among 5000 mother-child pairs randomly selected, 3069 were interviewed, and 2221 reported a previous HIV-negative test. From this group, we included 1714 mothers who had taken a new HIV test during the survey. Most of mothers included (83.3%,1428/1714) had a previous documented HIV test result and date. Median time from last test to survey was 15.5 months (IQR:8.0-25.9). A total of 57 new HIV infections were detected over 2530.27 person-years of follow-up. The estimated HIV incidence was 2.25 (95% CI: 1.74-2.92) per 100 person-years. Estimating HIV incidence among women who recently delivered using a community HIV-focused survey coupled with previous HIV-testing history based on patients' clinical documents is an achievable strategy.